Gpr54 deletion accelerates hair cycle and hair regeneration - Xia, Weili; Wang, Caibing; Guo, Biao; Tang, Zexin; Ye, Xiyun; Dang, Yongyan (EMBO reports, 2025)
GPR54, or KiSS-1R (Kisspeptin receptor), is key in puberty initiation and tumor metastasis prevention, but its role on hair follicles remains unclear. Our study shows that Gpr54 knockout (KO) accelerates hair cycle, synchronized hair regeneration and transplanted hair growth in mice. In Gpr54 KO mice, DPC (dermal papilla cell) activity is enhanced, with elevated expression of Wnts, VEGF, and IGF-1, which stimulate HFSCs. Gpr54 deletion also raises the number of CD34+ and Lgr5+ HFSCs. The Gpr54 inhibitor, kisspeptin234, promotes hair shaft growth in cultured mouse hair follicles and boosts synchronized hair regeneration in vivo. Mechanistically, Gpr54 deletion suppresses NFATC3 expression in DPCs and HFSCs, and decreases levels of SFRP1, a Wnt inhibitor. It also activates the Wnt/β-catenin pathway, promoting β-catenin nuclear localization and upregulating target genes such as Lef1 and ALP. Our findings suggest that Gpr54 deletion may accelerate the hair cycle and promote hair regeneration in mice by regulating the NAFTc3-SFRP1-Wnt signaling pathway. These findings suggest that Gpr54 could be a possible target for future hair loss treatments. Synopsis Gpr54 deletion lowers NFATC3 and SFRP1 levels, activates the Wnt/β-catenin pathway, which stimulates DPCs and HFSCs, and accelerates hair cycle and hair regeneration. Gpr54 knockout (KO) in mice accelerates the hair cycle, promotes synchronized hair regeneration, and enhances transplanted hair growth. Gpr54 KO increases DPC activity and stimulates HFSC proliferation. Gpr54 deletion reduces NFATC3 expression in DPCs and HFSCs, lowers SFRP1 levels and activates Wnt/β-catenin. The Gpr54 inhibitor, kisspeptin234, promotes hair growth and regeneration. Gpr54 deletion lowers NFATC3 and SFRP1 levels, activates the Wnt/β-catenin pathway, which stimulates DPCs and HFSCs, and accelerates hair cycle and hair regeneration.